INTRODUKSI FORMULA FUNGI MIKORIZA ARBUSKULA DARI RIZOSFER PISANG PADA BIBIT PISANG UNTUK PENGENDALIAN PENYAKIT DARAH BAKTERI (RALSTONIA SOLANACEARUM PHYLOTYPE IV) - Yefriwati, Yefriwati; Habazar, Trimurti; Husin, Eti Farda (JURNAL AGROTROPIKA, 2011)
Blood disease bacteria (BDB) caused by Ralstonia solanacearum Phylotype IV (Pseudomonas solanacearum) is one of the most important diseases on banana. Using biological agents such as arbuscular mycorrhizal fungi (AMF) to control BDB is still not maximal result, based on that need to search a potensial indigeneous AMF specific location. The aim of this experiment were to study the stability of formulated AMF indigenous to control BDB and to increase growth of banana seedlings. This research was arranged by Factorial in Randomized Complete Design (RCD) on green house experiment with 5 replicate. The treatment consist of 2 factors : 1) enrichment of carrier of AMF, sand with rock phosphate (0, 10, 20 and 40 %). 2) incubation periode (0, 1 and 2 months). Banana seedlings were intruduced with formulated AMF at planting date. Two month old banana seedlings were inoculated with Ralstonia solanacearum Phylotype IV. The parameter were observed include: incubation periode, disease insidence, disease severity, discoloration of pseudostem, population density of Ralstonia solanacearum Phylotype IV, colonisation degree of AMF on banana root, spore density on rhizosphere, growth of banana seedlings.The results showed that all formulated AMF introduced on banana seedlings reduced BDB development and increase banana growth compare with control plants, especially the formulated AMF enriched with 30 % rock phosphate.Key Words: arbuscular mycorrhizal fungi, blood disease bacteria, biological controll agents, banana